2013
DOI: 10.1302/0301-620x.95b11.32985
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral replacement

Abstract: Isolated patellofemoral arthritis is a common condition and there are varying opinions on the most effective treatments. Non-operative and operative treatments have failed to demonstrate effective long-term treatment for those in an advanced stage of the condition. Newer designs and increased technology in patellofemoral replacement (PFR) have produced more consistent outcomes. This has led to a renewed enthusiasm for this procedure. Newer PFR prostheses have addressed the patellar maltracking issues plaguing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…1). Twenty‐three cohort studies [1–3, 6, 16–18, 20, 32, 33, 39, 40, 50, 57, 64, 70, 71, 75, 84, 88, 92, 96, 102] and one registry [4] reported survivorship using Kaplan–Meier analysis. Forty‐two cohort studies [1–3, 6, 11, 13, 15–18, 20, 22, 24, 25, 30–33, 37, 39, 40, 45, 50, 51, 55, 57, 64, 65, 67, 70, 71, 73, 75, 84, 88–90, 92, 96, 98, 99, 102] and three registries [4, 9, 72] reported revision rates of which 22 cohort studies were published between 1995 and 2009 [1, 6, 13, 15, 16, 18,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Twenty‐three cohort studies [1–3, 6, 16–18, 20, 32, 33, 39, 40, 50, 57, 64, 70, 71, 75, 84, 88, 92, 96, 102] and one registry [4] reported survivorship using Kaplan–Meier analysis. Forty‐two cohort studies [1–3, 6, 11, 13, 15–18, 20, 22, 24, 25, 30–33, 37, 39, 40, 45, 50, 51, 55, 57, 64, 65, 67, 70, 71, 73, 75, 84, 88–90, 92, 96, 98, 99, 102] and three registries [4, 9, 72] reported revision rates of which 22 cohort studies were published between 1995 and 2009 [1, 6, 13, 15, 16, 18,…”
Section: Resultsmentioning
confidence: 99%
“…Forty‐two cohort studies [1–3, 6, 11, 13, 15–18, 20, 22, 24, 25, 30–33, 37, 39, 40, 45, 50, 51, 55, 57, 64, 65, 67, 70, 71, 73, 75, 84, 88–90, 92, 96, 98, 99, 102] and three registries [4, 9, 72] reported revision rates of which 22 cohort studies were published between 1995 and 2009 [1, 6, 13, 15, 16, 18, 24, 25, 32, 45, 50, 51, 55, 64, 65, 67, 73, 88–90, 92, 98] and 20 were published since 2010 [2, 3, 11, 17, 20, 22, 30, 31, 33,…”
Section: Resultsmentioning
confidence: 99%
“…[37][38][39] Those who choose PFA tend to feel that it represents a good bridging option to an eventually needed TKA and additionally affords faster recovery times, bone preservation, maintenance of ligamentous proprioception, and the ability to delay TKA. [4][5][6] In a retrospective, matched cohort study, it was found that PFA resulted in markedly better range of motion, higher Knee Society Score, and higher mean Forgotten Joint Score at both 1 and 3 years postoperatively than patients who received TKA for isolated PFOA. 40 Finally, one study has looked at the economic effect of PFA versus TKA and found that PFA may be economically superior in younger patients with Markov modeling showing that while PFA was more expensive than TKA ($49,811 versus $46,632, respectively), it was more effective over a lifetime (14.3 quality-adjusted life year gains vs 13.3 QALYS).…”
Section: Outcomes Of Patellofemoral Arthroplasty Versus Total Knee Ar...mentioning
confidence: 99%
“…Consistently, studies show that the most common reason for failure of PFA is progression of tibiofemoral OA with approximately 32% to 49% of revisions being done for this reason. 4-6,9,18-21,32,33 Other reasons for failure involve pain (16% to 17%), aseptic loosening (14%), patellar maltracking (6% to 10%), and infection (2% to 3%). 32,33 The two most common causes for PFA failure being progression of OA and pain highlight the importance of patient selection and indication for this procedure.…”
Section: Survival Data and Outcomes Of Patellofemoral Arthroplastymentioning
confidence: 99%
See 1 more Smart Citation